La confianza en el liderazgo genérala, consérvala - Evans, Christopher (Ideas en acción., 2017)
Trust is a mechanism of people's decision-making processes that mediates nearly every interaction in their lives. Identifying and discussing the specific issues or behaviors that increase or decrease one's willingness to trust--to be vulnerable to the actions of others--helps leaders increase their comfort in dealing with today's volatile, uncertain, complex, and ambiguous world. Developing fluency in initiating trust conversations helps both leaders and their colleagues open up to the possibility of creating greater responsibility throughout their relationships, teams, and business units.